Clinical course, causes of worsening, and outcomes of severe ischemic stroke: A prospective multicenter cohort study - Simiao Wu; Yanan Wang; Ruozhen Yuan; Meng Liu; Xing Hua; Linrui Huang; Fuqiang Guo; Dongdong Yang; Zuoxiao Li; Bihua Wu; Chun Wang; Jingfeng Duan; et al. (Chinese Medical Journal, 2025)
Abstract. Background:. Severe stroke has high rates of mortality and morbidity. This study aimed to investigate the clinical course, causes of worsening, and outcomes of severe ischemic stroke. Methods:. This prospective, multicenter cohort study enrolled adult patients admitted ≤30 days after ischemic stroke from nine hospitals in China between September 2017 and December 2019. Severe stroke was defined as a score of ≥15 on the National Institutes of Health Stroke Scale (NIHSS). Clinical worsening was defined as an increase of 4 in the NIHSS score from baseline. Unfavorable functional outcome was defined as a modified Rankin scale score ≥3 at 3 months and 1 year after stroke onset, respectively. We performed Logistic regression to explore baseline features and reperfusion therapies associated with clinical worsening and functional outcomes. Results:. Among 4201 patients enrolled, 854 patients (20.33%) had severe stroke on admission. Of 3347 patients without severe stroke on admission, 142 (4.24%) patients developed severe stroke in hospital. Of 854 patients with severe stroke on admission, 33.95% (290/854) experienced clinical worsening (median time from stroke onset: 43 h, Q1–Q3: 20–88 h), with brain edema (54.83% [159/290]) as the leading cause; 24.59% (210/854) of these patients died by 30 days, and 81.47% (677/831) and 78.44% (633/807) had unfavorable functional outcomes at 3 months and 1 year respectively. Reperfusion reduced the risk of worsening (adjusted odds ratio [OR]: 0.24, 95% confidence interval [CI]: 0.12–0.49, P <0.01), 30-day death (adjusted OR: 0.22, 95% CI: 0.11–0.41, P <0.01), and unfavorable functional outcomes at 3 months (adjusted OR: 0.24, 95% CI: 0.08–0.68, P <0.01) and 1 year (adjusted OR: 0.17, 95% CI: 0.06–0.50, P <0.01). Conclusions:. Approximately one-fifth of patients with ischemic stroke had severe neurological deficits on admission. Clinical worsening mainly occurred in the first 3 to 4 days after stroke onset, with brain edema as the leading cause of worsening. Reperfusion reduced the risk of clinical worsening and improved functional outcomes. Registration:. ClinicalTrials.gov, NCT03222024.